Comparative efficiency of compost, farmyard manure and sesbania green manure to produce rice-wheat crops under salt stressed environmental conditions - Sarwar, Ghulam; Malik, Muhammad Ashraf; Noor-Us-Sabah; Tahir, Mukkram Ali; Aftab, Muhammad; Manzoor, Muhammad Zeeshan; Zafar, Ayesha (Journal of Pure and Applied Agriculture, 2023)
: This study was planned to thrash positive effects of different organic amendments not only on yield of rice and wheat plants, but also on its role as a recovery agent. To achieve this purpose, sodic soil having pH = 8.75, TSS (total soluble salts) = 25.3 me L-1 , SAR (sodium adsorption ratio) = 25.65 (mmol.L -1 ) 1/2 was selected and filled in pots. Experiment consisted of 9 treatments that were repeated 4 times using a completely randomized design.